Foster-Kennedy syndrome – a case report - Świerczyńska, Aleksandra; Sobczak-Panek, Justyna; Woś, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
A 77-year-old female patient who had been treated for glaucoma for many years was referred to an outpatient clinic to extend the diagnostic work-up because of rapidly deteriorating vision despite anti-glaucoma treatment. During the visit, in addition to characteristic ophthalmic symptoms, behavioral and orientation disturbances were found, which raised a suspicion of Foster Kennedy syndrome and prompted the examining physician to refer the patient for an urgent brain scan. A computed tomography examination revealed the presence of focal lesions. Rapid diagnosis enabled immediate transfer of the patient to a neurosurgical center for further treatment.